2022
DOI: 10.7717/peerj.14046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of road traffic injuries and casualties in China: a ten-year nationwide longitudinal study

Abstract: Background Road traffic injuries (RTIs) are a serious global problem, and a huge challenge for both economic development and public health. Methods This longitudinal study was based on the national data from Chinese authorities. Descriptive analysis was utilized to analyze the prevalence and trend of RTIs among different types, groups and regions. In addition, ridge regression or/and curve regression were also used to explore the relationship between those possible influencing factors and RTIs. Results Fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, the frequency of road accident both in western and eastern fluctuated from 2016 to 2019, with an overall trend of increasing. This trend was also confirmed by recently published literature ( 36 ). The authors considered that the reasonable explanation may be the continuous progress urbanization and the increase in traffic flow ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the frequency of road accident both in western and eastern fluctuated from 2016 to 2019, with an overall trend of increasing. This trend was also confirmed by recently published literature ( 36 ). The authors considered that the reasonable explanation may be the continuous progress urbanization and the increase in traffic flow ( 37 ).…”
Section: Discussionsupporting
confidence: 91%
“…Road traffic injuries (RTIs) has not only become a social safety problem that cannot be ignored worldwide ( 1 , 2 ), but a huge challenge to economic development and public health as well ( 3 ), with the development of motorization rapidly. The Global Status Report on Road Safety 2018 showed that around 1.35 million people worldwide died from RTIs each year, and 50 million people suffered non-fatal injuries from traffic crashes, some disabled as a result among them ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, although some studies have reported that RTIs showed a downward trend attributed to road safety laws and various policies in China, the mortality of RTIs is still much higher than that in developed countries ( 9–11 ). As a result, it is still a very serious problem in China that should be paid more attention to ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, traumatic injury causes more than 700 thousand deaths each year, accounting for 9% of all deaths and ranking as the fifth leading cause of death [ 2 ]. Among the mechanisms, with the development of society, traffic accidents have become the main cause of injury; the overall mortality rate of traffic accidents could be up to 33.87%, especially in China and other countries [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%